"(9x^2y^3)(7xy^2)"

Question

Asked 12/10/2011 10:11:06 PM

Updated 7/21/2014 12:25:37 PM

1 Answer/Comment

Flagged by andrewpallarca [7/21/2014 12:25:36 PM]

Question

Asked 12/10/2011 10:11:06 PM

Updated 7/21/2014 12:25:37 PM

1 Answer/Comment

Flagged by andrewpallarca [7/21/2014 12:25:36 PM]

Rating

3

(9x^2y^3)(7xy^2) = 63x^3y^5

Added 7/21/2014 12:25:37 PM

This answer has been confirmed as correct and helpful.

Factor completely, showing work: 7x^2-5x-2

Question

Not Answered

Updated 7/12/2014 12:31:28 PM

1 Answer/Comment

Simplify 7x + 4 + 3x - 3

Question

Expert Answered

Updated 12/10/2011 10:38:50 PM

1 Answer/Comment

7x + 4 + 3x - 3 simplifying 10x+1

Added 12/10/2011 10:38:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/21/2014 12:32:42 PM]

Solve using PEDMAS: 8 x 2 +9 / 3 **Weegy:** The answer is 19 (More)

Question

Expert Answered

Updated 7/21/2014 12:32:58 PM

1 Answer/Comment

8 x 2 +9 / 3

= 16 + 3

= 19

= 16 + 3

= 19

Added 7/21/2014 12:32:58 PM

This answer has been confirmed as correct and helpful.

Multiply: (x + 2)(x^2 + 3x - 4) **Weegy:** Move like terms to opposite sides and we have: x=-6 (More)

Question

Expert Answered

Updated 7/21/2014 12:27:38 PM

2 Answers/Comments

(x 2)(x^2 3x - 4) assuming that this is (X^2)(x^2+3x-4) then x^4+3x^3-4x^2 is the answer.

Added 12/10/2011 10:31:15 PM

This answer has been flagged as incorrect.

Flagged by andrewpallarca [7/21/2014 12:27:43 PM]

(x + 2)(x^2 + 3x - 4)

= x^3 + 3x^2 + 2x^2 - 4x + 6x - 8

= x^3 + 5x^2 + 2x - 8

= x^3 + 3x^2 + 2x^2 - 4x + 6x - 8

= x^3 + 5x^2 + 2x - 8

Added 7/21/2014 12:27:38 PM

This answer has been confirmed as correct and helpful.

Solve for x: "-2(x - 4) = -3(x + 8)" **Weegy:**
-2(x - 4) = -3(x + 8),
-2x + 8 = -3x - 24,
-2x + 3x = -24 - 8,
x = -32
(More)

Question

Expert Answered

Updated 7/21/2014 12:35:06 PM

0 Answers/Comments

27,208,668

questions answered

There are no comments.